Evaluation of Geomorphological Capabilities in Kermanshah Province in Locating Sensitive and Important Centers with Passive Defense Approach - zahra heidari; asadolah heqazi; shahram rostaei; siros fakhri (تحقیقات کاربردی علوم جغرافیایی, 2024)
Given Iran's ongoing role in the Middle East and the constant threat of external threats, it is imperative that I take action on the critical and important steps of my country Of the measures that can prevent the occurrence of malignancies , Kermanshah region due to its geographical location and proximity to Iraq as well as its complex morphology include high mountainous lands, relatively wide valleys and plains, geological structural diversity and With the immediate approach, Identify these natural features It creates the right places With passive defense approach To establish these centers. In this research, the research tools are surveyed topographic maps, geology and satellite and aerial images of the area as well as interviews with experts identifying the effective factors in locating critical and important centers with emphasis on passive defense..And after identifying them using AHP (Multi Criteria Decision Making Models) in order to compare the criteria has been analyzed. Also according to the final map based on geomorphological factors in ARC- GIS software environment The area of optimum area for the location of critical and sensitive areas in the northern part is greater than the soothe In other words, the geomorphologic features of the region in the northern and eastern parts of the region are more favorable than those in the western and southern regions for the optimal location of sensitive and important sites.